The effect of business strategy, innovation, organizational culture on the performance of micro small medium enterprises (MSMES) moderated by financial literature - Nursetiana, Nursetiana; Hanifah, Imam Abu; Ismawati, Iis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research purpose is to empirically analyze the effect of business strategy, innovation, organizational culture, on the performance of MSMEs moderated by financial literacy in Banten Province. This study uses a sample of Small and Medium-scale SMEs in Banten Province. The data used is primary data. The data in the study were obtained from the results of questionnaires distributed to 100 MSME entrepreneurs in Banten Province both directly and online through the google form. Structural Equation Modeling is used as an analysis with the help of Smart SPSS software version 25. The results of this study indicates that Business Strategy, Innovation, and Organizational Culture have a positive effect on the performance of MSMEs in Banten Province, and Finacial Literacy able to moderated Business Strategy, Innovation, and Organizational Culture on performance of MSMEs in Banten Province.